2012
DOI: 10.1103/physrevb.86.115333
|View full text |Cite
|
Sign up to set email alerts
|

Spin coherence generation in negatively charged self-assembled (In,Ga)As quantum dots by pumping excited trion states

Abstract: Spin coherence generation in negatively charged self-assembled (In,Ga)As quantum dots by pumping excited trion states PHYSICAL REVIEW B, COLLEGE PK, v. 86, n. 11, supl Spin coherence generation in an ensemble of negatively charged (In,Ga)As/GaAs quantum dots was investigated by picosecond time-resolved pump-probe spectroscopy measuring ellipticity. Robust coherence of the ground-state electron spins is generated by pumping excited charged exciton (trion) states. The phase of the coherent state, as evidenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
3
1
2
Order By: Relevance
“…Thus, in the fast dephasing approximation, φ is always zero, irrespective of the strength of the applied magnetic field, electron or hole g factor, trion lifetime, the specific QD singlet photoexcitation, and the QD band gap. This contradicts a previous investigation that has shown that the phase depends on the QD band gap [13]. Figure 2 shows the phase extracted by fitting the longterm (t > 0.5 ns) magnetization oscillation, using (1), for a sample containing ten layers of negatively charged (In,Ga)As QDs, whose fundamental energy gap is resonant with a laser wavelength of 915 nm.…”
contrasting
confidence: 61%
“…Thus, in the fast dephasing approximation, φ is always zero, irrespective of the strength of the applied magnetic field, electron or hole g factor, trion lifetime, the specific QD singlet photoexcitation, and the QD band gap. This contradicts a previous investigation that has shown that the phase depends on the QD band gap [13]. Figure 2 shows the phase extracted by fitting the longterm (t > 0.5 ns) magnetization oscillation, using (1), for a sample containing ten layers of negatively charged (In,Ga)As QDs, whose fundamental energy gap is resonant with a laser wavelength of 915 nm.…”
contrasting
confidence: 61%
“…10 The use of hot trions enables the control of the spatial extent of carrier wavefunctions and the spin manipulation via optical pumping resonant to the P-Shell. 11,12 From these findings, it is concluded that the detailed knowledge of the QD electronic structure is required for the generation and management of multiparticle exciton species with interesting emission properties for quantum information technologies.…”
mentioning
confidence: 99%
“…Next, a sequence that consists of a Si d-doping layer, 15 nm GaAs, 2.4 monolayer (ML) InAs, 15 nm GaAs, a Si d-doping layer, and 20 nm GaAs was repeated ten times. The d-doping layers were inserted to obtain an average occupation of one electron per QD, 19 but are of no further interest in the current study. Finally, the sample was capped with 45 nm GaAs.…”
mentioning
confidence: 99%